Membangun Semangat Belajar melalui Nilai Religius: Peran Strategis Guru di Madrasah Ibtidaiyah Negeri 06 Aceh Tengah - Asdiana Diana; Ayumi (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2026)
Teachers play a strategic role in education as their presence greatly determines the quality and success of the learning process. Their duties cover professional, humanitarian, and social aspects which are manifested in various forms of dedication. In the professional domain, teachers act as educators, instructors, and trainers. This study aims to examine the role of teachers in improving students’ learning motivation during, to identify the obstacles they face, and to analyze the efforts made to overcome these challenges. The research employed a qualitative descriptive method conducted at MIN 06 Aceh Tengah. Data were collected through interviews, observation, and documentation. The findings reveal that the role of teachers in enhancing the learning motivation of fifth-grade students (Class V/A) has been implemented effectively. These roles include teachers as facilitators, directors, transmitters, and motivators. Therefore, teachers’ roles are not only limited to delivering knowledge but also to fostering students’ motivation to be more active and enthusiastic in learning. Keywords: teacher, learning motivation, teacher’s role.